Compensatory Growth and Feed Utilization of Humpback Grouper, Cromileptes altivelis Receiving Preset Period of Unfed-Fed Cycle - Edy Yuwono; Purnama Sukardi (Fakultas Biologi | Universitas Jenderal Soedirman, 2007)
The effect of preset periods of unfed-fed cycle on growth, feed efficiency and body condition indices of humpback grouper, Cromileptes altivelis was studied. The fish receiving non-feeding/feeding cycle of 1/2 day (T1); 1/2 and 3 days alternately (T2); 1/3 day (T3); were compared to that fed daily as a control (C). Each feeding treatment was assigned to five fiberglass tanks according to a completely randomized design. All fish was weighed to obtain final weight gain at the end of the experiment. Feeding rate (FR) was calculated during feeding period throughout the experiment. At the end of the experiment all fish was weighed to obtain final fish weight. Absolute growth rate (AGR); survival; consumption; cumulative feed consumption, and feed conversion efficiency (FCE) were calculated. Data were subjected to analysis of variance and Tukey test (P<0.05). The results showed that humpback grouper Cromileptes altivelis receiving preset unfed-fed cycle elicited compensatory growth and the fish showed hyperphagia and greater feed conversion efficiency.